Hearing Nature: Approaching International Environmental Communication through Music and Sound - Titus, Joshua Groffman, Olusegun Stephen (The Handbook of International Trends in Environmental Communication, 2021)
This chapter provides an overview of recent work done in the interdisciplinary field of ecomusicology: the study of “music, culture, and nature in all the
Keywords: dept.mus